Evaluation of Parasitic Diseases in Patients Brought to Fırat University Animal Hospital - Gündoğ, Sıla Özgür; Çelik, Figen; Şimşek, Sami (Galenos Publishing House, 2021)
Objective: This study was aimed to evaluate the parasitic diseases in patients brought to Firat University Animal Hospital (FUAH) between 1972 and 2019. Methods: Patient records between 03.31.1972 and 06.02.1982 and between 04.24.2012 and 15.09.2019 in the archive of FUAH were checked. Results: In the mentioned period, 50.17% of the patients that applied to FUAH were cattle, 18.42% were dogs, 13.04% were horses, 10.7% were sheep, 3.26% were cats, 3.18% were goats, and 1.2% were other animals (rabbit, ornamental birds, donkey, and chicken). In this period, various parasitic diseases were detected in 1.411 (3.83%) of a total of 36,763 patients brought to FUAH. Considering the distribution of parasitic diseases according to animal species, the most ascariosis cases (46.19%) were detected in horses, followed by strongylosis and strongylosis+ascariosis mixed infections. In the second phase, dogs had the highest cases of ascariosis (43.07%), followed by scabies and coccidiosis. While ectoparasites, such as lice, fleas, and ticks, were encountered in a lesser ratio, leishmaniasis, a zoonotic infection, was also observed. In cattle, 41.95% of the parasitic diseases diagnosed were theileriosis, followed by coccidiosis, babesiosis, and leech cases. Conclusion: The results of this study reveal that the variety of parasitic diseases changes with season and that control strategies should be diversified with this situation. © 2021 Turkish Society for Parasitology.
Fırat Üniversitesi Hayvan Hastanesi’ne Başvuran Hastaların Paraziter Hastalıklar Yönünden Değerlendirilmesi
Keywords: Fırat University Animal Hospital; Parasitic diseases; prevalance